The Role of Village Government Policies in Improving the Economy in Sumbermulyo Village - Fatimatuz Zuhriyah; Sidrotun Naim; Deden Rahmanudin; Febby Widjayanto; Sabil Mokodenseho (Jurnal Kewarganegaraan, 2022)
AbstractThis study aims to analyze the role of the Sumbermulyo Village government in improving the economy of the farming community. Qualitative descriptive method with phenomenological approach was used to analyze the data. This research was conducted because the number of people in Sumbermulyo Village who still choose to farm is getting smaller. People are more interested in working as employees in a company, as well as government and private agencies because the agricultural sector is considered unpromising in terms of income. Research shows that the majority of the community, especially youth graduates from high school or equivalent, do not continue their education to college but prefer to work as traders and laborers, as well as company employees outside the region. From this problem, the shift of the farming community from the old one will gradually be replaced by the younger generation. This study concludes that the actual efforts made by the village government have been quite good. However, the competition between the agricultural and industrial sectors in Sumbermulyo Village is quite fierce. This competition can be seen from differences in income, working hours, facilities and prestige which makes many young people prefer other professions than farming. Moreover, parents agree and support the change of profession from parent to child. This study suggests that the village government can anticipate it by providing counseling and training as well as motivating the community that the agricultural sector is one of the most important sectors in improving the economy.Keywords: Village Government, Village Economy, Farmer Community, Village Potential